اتجاهات المواطنين الليبيين نحو ثورة 17 فبراير الدوافع الحقيقية و عوامل النجاح - جبران الكرغلي, د.صبري; محمد القماطي, د.يوسف (Scientific Journal of University of Benghazi, 2026)
This paper seeks to assess the Libyans attitudes towards the 17th of February Libyan Revolution. The paper tries to achieve three main objectives: (1) to determine the meaning of 17th of February Revolution success. (2) to determine the degree of revolution success. (3) to assess the future of new Libya based on respondents' views. (4) to identify the revolutions' motivations. (5). To indentify the key success factors of the revolution. In terms of research methodology, questionnaire survey was designed particularly for this research and assessed by 8 scholars to ensure high validity and reliability of the construct content. A number of (500) questionnaires were circulated to residents in Benghazi, the second Largest city in Libya. Out of this number, (325) were returned with (268) deemed valid for analysis. Descriptive statistical analysis was used and one-way analysis of variance (ANOVA) or Kruskal-Wallis (KW) were used as well to test the research hypotheses. The major variables of study are: revolution success meaning, revolution success degree, future of Libya, revolution's motivations, and revolution's key success factors.